Listening to the land : Native American literary responses to the landscape - Schweninger, Lee (University of Georgia Press, 2008)
"Looks at the challenges faced by Native American writers who confront stereotypical representations as they assert their own ethical relationship with the earth. Lee Schweninger considers a range of genres by Native writers from various parts of the United States. Contextualizing these works within the origins, evolution, and perpetuation of the 'green' labels imposed on American Indians, Schweninger shows how writers often find themselves denying some land ethic stereotypes while seeming to embrace others"--Publisher description